Work family conflict among teachers: evaluating measurement model fit - R Ibrahim, R Zirwatul Aida; Mat Ali, Siti Nazilah; Abu Bakar, Azlina; Mohd Dagang, Mazidah; Omar, Khatijah; Johar, Siti Sarawati (ASIAN INSTITUTE OF TECHNOLOGY, 2018)
Work family conflict issue has received increasing attention by researchers involving the psychometric properties of measurement scale and its factor structures. Thus, the present study evaluated the psychometric properties and confirmed the factor structure of the work family conflict. A survey design using self-administered questionnaire was conducted to collect the data from 487 teachers in East Coast of Malaysia (Kelantan, Terengganu and Pahang) through multistage-random sampling technique. Results of exploratory factor analysis performed using Principal Component Analysis (PCA) yielded two factor structures with the cut off value of loading factor (λx) is 0.50 with rotated solution is Varimax. Further, the confirmatory factor analysis (CFA) also confirmed the scale as a two model factor with good fit indices of p<0.01, χ2 /df=2.41, RMSEA=0.05, CFI=0.99, PCFI=0.63. All items also yielded acceptable factor loading (λx) ranging from 0.72 to 0.94. Thus, the work family conflict scale is a valid and reliable instrument among Malay speaking teachers in the East Coast of Malaysia and proved as a two factor models (e.g. work conflict and family conflict) as the best model fit. Benefits of the measure and uses are discussed.